Molecular detection of qnrA and qnrB genes in uropathogenic eshcerichia coli (UPEC) isolates from Perak - An, Hui Ching (2023)
Uropathogenic E. coli (UPEC) is the causative agent in most urinary tract infection (UTI) cases in Malaysia. The overuse of fluoroquinolone antibiotics in treating UTI had been the major cause for the emergence of fluroquinolone antibiotic resistant strains. Several resistance genes had contributed the fluoroquinolone resistance in UPEC, including the qnrA and qnrB genes. Randomised samples of 75 UPEC clinical isolates had been collected from Hospital Permaisuri Bainun, Ipoh. In this study, the antibiotic resistance rate of the isolates were evaluated. The UPEC isolates were observed to be highly resistant to ampicillin (74.67%), followed by nalidixic acid (60%), levofloxacin (48%), ciprofloxacin (41.33%), and 36% for trimethoprim-sulfamethoxazole (SXT). None of the isolates were resistant to imipenem and tobramycin, while 20% and 2.67% of the isolates were resistant to gentamicin and amikacin respectively. Total DNA was extracted from each isolate and duplex PCR was carried out to detect for qnrA and qnrB genes. The qnrB gene was found to be more prevalent than qnrA, as 4.17% (2/48) of isolates resistant to the fluoroquinolone antibiotics (ciprofloxacin, nalidixic acid, levofloxacin) carried qnrB, while none of the isolates carried qnrA gene. No isolates sensitive to iii fluoroquinolone harboured qnrA and B genes. No significant association had been found between the targeted qnr genes and fluoroquinolone resistance rate in the UPEC isolates.